India and her South Asian neighbours - Bastiampillai, Bertram (Colombo : Bandaranaike Centre for International Studies, S.W.R.D. Bandaranaike National Memorial Foundation, 1992)
Seminar papers.
Keywords: India -- Relations -- South Asia -- Congresses; South Asia -- Relations -- India -- Congresses